Deconstructing Anthropocentric Sustainability: A Post-Anthropocentric Critique of Halal Tourism Ecosystem - Mohammad Aliman Shahmi; Yuliza Zen; Rizal Rizal; Chitra Indah Sari (Imara: Jurnal Riset Ekonomi Islam, 2025)
Background: Halal tourism has expanded rapidly, often adopting the narrative of "sustainable economics" as part of its value proposition. However, the dominant global sustainability paradigm—including that implicit in many Sustainable Development Goals (SDGs) frameworks—is fundamentally anthropocentric, prioritizing human economic and social interests above all else. A conceptual paradox arises when this anthropocentric framework is applied to "halal" ecosystems, which are essentially theocentric, positioning humanity as khalifah (steward), not owner, of nature. Purpose : The purpose of this study is to deconstruct the "anthropocentric sustainability" concept that has permeated halal tourism models. This research aims to provide a post-anthropocentric critique of how contemporary halal tourism ecosystems operate, highlighting the tensions between human-centric sustainability rhetoric and the imperatives of Maqashid al-Shariah (particularly Hifz al-Bi'ah or environmental protection). Method : This study  uses a library research utilizing a critical conceptual analysis approach. This study systematically reviews, analyzes, and synthesizes interdisciplinary literature across three domains: (1) critical sustainability theory and anthropocentrism, (2) tourism economics, and (3) Islamic economic philosophy and halal tourism.. Result : Findings (Arguments) indicate that the adoption of anthropocentric sustainability models often results in "greenwashing" or "halal-washing," where nature remains exploited as a "resource" for human profit, contradicting the principle of amanah. As an alternative, this paper proposes a shift towards a post-anthropocentric (theocentric) framework for halal tourism, one that authentically integrates ecological preservation as a spiritual and ethical objective, not merely an economic instrument. This research contributes to a reconceptualization of halal tourism that moves beyond anthropocentrism toward a holistic and theologically authentic sustainability model